2014
DOI: 10.1038/cddis.2014.256
|View full text |Cite
|
Sign up to set email alerts
|

EZH2-mediated epigenetic suppression of long noncoding RNA SPRY4-IT1 promote s NSCLC cell proliferation and metastasis by affecting the epithelial–mesenchymal transition

Abstract: Recent evidence indicates that long noncoding RNAs (lncRNAs) have a critical role in the regulation of cellular processes such as differentiation, proliferation, and metastasis. These lncRNAs are dysregulated in a variety of cancers and many function as tumor suppressors; however, the regulatory factors involved in silencing lncRNA transcription are poorly understood. In this study, we showed that epigenetic silencing of lncRNA SPRY4 intronic transcript 1 (SPRY4-IT1) occurs in non-small-cell lung cancer (NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(189 citation statements)
references
References 36 publications
8
177
2
Order By: Relevance
“…For PDCD1LG2 and PKD2, there was no publication suggesting their roles in NSCLC. In contrast, the EZH (enhancer of zeste homolog) family appears to play an important role in NSCLC [22][23][24][25][26]. Thus, we explored if EZH1 is a target of miR-17-5p and there was a good alignment between 3 0 -UTR of EZH1 mRNA and miR-17-5p seed sequence (Figure 4(A)).…”
Section: Ezh1 Is a Target Of Mir-17-5pmentioning
confidence: 99%
“…For PDCD1LG2 and PKD2, there was no publication suggesting their roles in NSCLC. In contrast, the EZH (enhancer of zeste homolog) family appears to play an important role in NSCLC [22][23][24][25][26]. Thus, we explored if EZH1 is a target of miR-17-5p and there was a good alignment between 3 0 -UTR of EZH1 mRNA and miR-17-5p seed sequence (Figure 4(A)).…”
Section: Ezh1 Is a Target Of Mir-17-5pmentioning
confidence: 99%
“…85 A recent study in non-small cell lung cancer (NSCLC) has found evidence that SPRY4-IT1 controls epithelial-mesenchymal transition (EMT) through regulation of E-cadherin and vimentin expression leading to cell proliferation and metastasis. 86 …”
Section: Spry4-it1mentioning
confidence: 99%
“…For instance, a lncRNA named SPRY4 intronic transcript 1 (SPRY4-IT1) was reported to be overexpressed in melanoma, renal cell carcinoma, esophageal squamous cell carcinoma, breast cancer, bladder cancer and glioma, and associated with poor prognosis and promotion of tumor growth (24)(25)(26)(27)(28)(29). Certain studies also demonstrated that SPRY4-IT1 expression was decreased in non-small-cell lung cancer and gastric cancer, and acted with significant antitumor function in these two types of cancer (30,31). Similarly, HOTTIP may exhibit a tissue-specific expression pattern and serve a different function in different types of cancer, as with SPRY4-IT.…”
Section: Discussionmentioning
confidence: 99%